Technology Innovations to Enhance Livestock Agribusiness - Rutledge, J J (Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
In vitro embryo production (IVP) offers a way to build a sustainable and productive dairy cattle industry in tropical areas. For about 100 years breeding efforts have centered on synthetic breed formation without success, but this 100 year effort reaffirms the superiority of the first cross of Bos taurus and B. indicus and generally, the inferiority of all crosses subsequent to the first . IVP permits the limiting life history characteristics of low reproductive rate and 1 : 1 sex ratio to be circumvented. There are no remaining technological barriers to implementation . Since B. javanicus has higher tropical adaptation than B. indicus, it is suggested that first crosses of this species with B. taurus be evaluated. Key word: In vitro embryo production, B. javanicus, B. indicus, B. taurus, agribusiness